ICTs in the banking sector in the times of the COVID-19 pandemic: the customer’s perspective - Piotrowski, Dariusz (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The digitization of financial services has brought a noticeable decline in the importance of branch banking for customers wanting to contact their bank or receive financial services. The lack of personal contact with bank employees has become particularly significant during the pandemic, with remote modes of communication reducing the risk of contracting SARS-CoV-2. Aim: The present study applies the Spearman’s rank correlation coefficient and binomial logit model to determine the impact of the digitization of bank services and the COVID-19 pandemic on retail customers’ needs for branch banking. Results: The empirical research conducted demonstrated that the factors significantly positively influencing the need to use financial services provided by staff in bank branches were respondent experience in using bank advisory services and fear of interpersonal contact in the pandemic context. Meanwhile, variables with a negative effect were the use of the electronic banking platform, attitudes towards the use of the artificial intelligence technology in the banking sector, and perceptions of the advantages of remote communication with institutions in the pandemic context.